1999
DOI: 10.1348/026151099165384
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition and bullying: Social inadequacy or skilled manipulation?

Abstract: In contrast to the popular stereotype and research tradition of the ‘oafish’ bully lacking in social skills and understanding, the bully may be a cold, manipulative expert in social situations, organizing gangs and using subtle, indirect methods. Performance on a set of stories designed to assess understanding of cognitions and emotions was investigated in 193 7‐10‐year‐olds in relation to role in bullying. Ringleader bullies scored higher than ‘follower’ bullies (those who helped or supported the bully), vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
421
11
56

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(518 citation statements)
references
References 48 publications
30
421
11
56
Order By: Relevance
“…Victims (Woods et al 2009) and those exhibiting symptoms of depression (Beck 2008;Evans et al 2005) have been shown to have numerous biases in cognitive processing, e.g., deeper encoding of negative information in memory or interpretation of ambiguous material as negative (Dearing and Gotlib 2009;Hertel and Brozovich 2010). Thus being victimized, in particular if chronic or severe, may work itself into the brain altering neuro-circuitry and social cognition (Gini 2006;Sutton et al 1999;Teicher et al 2010) and stress response (Ouellet-Morin et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Victims (Woods et al 2009) and those exhibiting symptoms of depression (Beck 2008;Evans et al 2005) have been shown to have numerous biases in cognitive processing, e.g., deeper encoding of negative information in memory or interpretation of ambiguous material as negative (Dearing and Gotlib 2009;Hertel and Brozovich 2010). Thus being victimized, in particular if chronic or severe, may work itself into the brain altering neuro-circuitry and social cognition (Gini 2006;Sutton et al 1999;Teicher et al 2010) and stress response (Ouellet-Morin et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These "bully victims" have been characterized as hyperactive, impulsive, and as experiencing more peer rejection, more academic difficulties, and more stressful and harsh home environments (see Schwartz, Proctor, & Chien, 2001), but represent only a small portion (1% to 12%) of students (Dulmus et al, 2006;Nansel et al, 2001;Solberg & Olweus, 2003;Spriggs, Iannotti, Nansel, & Haynie, 2007). Over the past four decades, research has also shown that many bullies are socially intelligent (Björkqvist, Österman, & Kaukiainen, 2000;Sutton, Smith, & Swettenham, 1999a, 1999b and enjoy considerable status in the peer group (Vaillancourt et al, 2003), leading to distinctions between socially marginalized and socially integrated bullies (Farmer et al, 2010). Adults may be less able to recognize bullying perpetrated by students who appear to be socially competent, wellfunctioning individuals.…”
Section: Different Types Of Bulliesmentioning
confidence: 99%
“…The sole exception might be the putative link between theory of mind and proactive aggression, which might be stronger for boys than for girls. This expectation was based on the fact that theory of mind was positively related to bullying behavior only in boys but not girls in one study (Caravita et al 2010), although gender-specific correlations were not reported in another study (Sutton et al 1999). …”
Section: Gender Effectsmentioning
confidence: 99%
“…Children with high theory of mind skills may deliberately choose aggressive behavior in some social situations because they expect it to be effective for achieving personal gains. Some, albeit indirect evidence in support of this notion comes from findings that theory of mind is positively related to bullying behavior (Caravita et al 2010;Sutton et al 1999) and to children's ability to lie in a consistent fashion (Talwar et al 2007). To date, however, no study has directly examined the possibility of a differential relation of theory of mind with reactive and proactive aggression, respectively.…”
Section: Theory Of Mindmentioning
confidence: 99%
See 1 more Smart Citation